Hospital Readmission From the Perspective of Medicaid and Uninsured Patients. Issue 1 (January 2018) - Misky, Gregory J.; Burke, Robert E.; Johnson, Teresa; del Pino Jones, Amira; Hanson, Janice L.; Reid, Mark B.
Abstract : Background: Patients with little or no health insurance are frequently readmitted to the hospital, yet few previous studies have listened to patients' explanations of why they returned to the hospital after discharge. Enhanced understanding of patient perspectives may facilitate targeted services and improve care. Methods: We enrolled 18 patients with Medicaid or no insurance during a hospital readmission within 30 days in a major metropolitan area, and conducted semi-structured qualitative interviews to explore the impact of patients' experiences around readmission using a grounded theory approach. Results: We identified five themes contributing to readmission: (1) therapeutic misalignment; (2) accountability; (3) social fragility; (4) access failures; and (5) disease behavior. Medical conditions were complicated by social influences and insufficiently addressed by our health system. Patients understood the need to manage their own health but were unable to effectively execute care plans because of competing life demands and compromised relationships with health providers. Conclusions: Our study using interviews of readmitted Medicaid and uninsured patients revealed complex illnesses complicated by social instability and health system failures. Improved patient-provider trust and shared decision-making, while addressing social determinants and expanding care coordination with community partners, provide opportunity to better meet patients' needs and decrease hospital readmission in high-risk patients. Abstract : Supplemental Digital Content is Available in the Text.